Prevalence of HIV-related risk behaviors in the general population of Malakand division, Khyber Pakhtunkhwa: A community cross-sectional survey - Nisar, Muhammad; Ahmad, Dureem; Ullah , Rasheed (Infectious Diseases Journal of Pakistan, 2025)
Background: HIV-related risk behaviors are grossly under-reported in rural Pakistan despite their public health addresses. It is important to know its frequency in Malakand Division for prevention strategies. Material and Methods: A community-based cross-sectional study was conducted in eight districts of Malakand Division, Khyber Pakhtunkhwa, from January 2023 to December 2024. A random sample of 2,630 individuals (≥15 years) was surveyed through interviewer-administered home questionnaires on sexual practices, substance use, and socio-behavioural risks. Data were analyzed using SPSS v26, with results presented as counts and percentages. Results: The number of male participants was 1,595 (60.6%) and female participants were 1,035 (39.4%). Unprotected sex was 210/300 (70.0%) in Dir Upper and 150/250 (60.0%) in Shangla vs. 20/52 (38.5%) for Chitral). IV drug sharing was more prevalent in Chitral (10/52, 19.2%) than Swat district (38/480, 7.9%). Polygamous relations were seen in 15/100 (15.0%) of the Swat and 15/52 (28.8%) of Chitral group. Sex work was reported by 10/110 (9.1%) in Buner and 10/52 (19.2%) in Chitral. Highest rate of alcohol use was observed in patients from Dir Upper (120/300, 40.0%) followed by Shangla (90/250, 36.0%). Child marriage was prevalent in Shangla (35/250, 14.0%) and Chitral (8/52, 15.4%). Conclusion: HIV-related risk behaviours were regionally diverse; unprotected sex and substance use was common in Dir Upper and Shangla, whereas needle sharing and multiple partners was more prevalent among people from Chitral. Keywords: Adolescent, HIV Infections/ epidemiology, Pakistan, Risk-Taking, Sexual behavior, Substance-Related disorders, Unsafe sex.